Distribusi Bantuan Sosial dalam Perspektif Keadilan: Studi di Desa Tasik Raya Kabupaten Indragiri Hilir - Misran; Jamri; Herdiansyah (PT PUSTAKA CENDEKIA GROUP, 2026)
Social assistance is a form of the state's responsibility to promote public welfare, particularly for poor and vulnerable communities. However, its implementation still faces various challenges, resulting in distribution that is not entirely fair or well-targeted. This study aims to examine the mechanism of social assistance distribution in Tasik Raya Village, Indragiri Hilir Regency, analyze its implementation from the perspective of justice, and identify the factors hindering fair distribution. This research employed a sociological (empirical) legal research method with a descriptive-analytical approach. Data were collected through interviews with the Village Head, village officials, neighborhood leaders (RT/RW), and community members, supported by a literature review of relevant laws, books, and academic journals. The data were analyzed qualitatively. The findings indicate that the distribution mechanism consists of community data collection by RT/RW, verification by the village government, village deliberation, and the distribution of assistance to eligible beneficiaries. Nevertheless, the implementation has not fully reflected the principles of social justice, as some ineligible individuals still received assistance while certain eligible low-income residents were excluded. The main obstacles include inaccurate beneficiary data, limited assistance quotas, lack of transparency, social proximity factors, low community participation, weak inter-agency coordination, and limited public understanding of beneficiary eligibility criteria. Therefore, regular data updates, improved transparency, and strengthened community oversight are necessary to ensure that social assistance distribution becomes fairer and more accurately targeted.